The Interaction between Auxin and Nitric Oxide Regulates Root Growth in Response to Iron Deficiency in Rice - Sun, Huwei; Feng, Fan; Liu, Juan; Zhao, Quanzhi (Frontiers in Plant Science, 2017)
Fe deficiency (–Fe) is a common abiotic stress that affects the root development of plants. Auxin and nitric oxide (NO) are key regulator of root growth under –Fe. However, the interactions between auxin and NO regulate root growth in response to Fe deficiency are complex and unclear. In this study, the indole-3-acetic acid (IAA) and NO levels in roots, and the responses of seminal root growth in rice to different levels of Fe supply were investigated using wild type (WT), ospin1b and osnia2 mutants. –Fe promoted LR formation but inhibited seminal root elongation. IAA levels, [3H] IAA transport, and expression levels of PIN1a-c genes in roots were reduced under –Fe, suggesting that polar auxin transport from shoots to roots was decreased. Application of IAA to –Fe seedlings restored seminal root length, but not LR density, to levels similar to those under normal Fe (+Fe), and the seminal root length was shorter in two ospin1b mutants relative to wild-type (WT) under +Fe, but not under –Fe, confirming that auxin transport participates in –Fe-inhibited seminal root elongation. Moreover, –Fe-induced LR density and –Fe-inhibited seminal root elongation paralleled NO production in roots.. Interestingly, similar NO accumulation and responses of LR density and root elongation were observed in osnia2 mutants compared to WT, and the higher expression of NOA gene under –Fe, suggesting that –Fe-induced NO was generated via the NO synthase (NOS)-like pathway rather than the nitrate reductase (NR) pathway. However, IAA could restore the functions of NO in inhibiting seminal root elongation, but did not replace the role of NO-induced LR formation under –Fe. Overall, our findings suggested that NO functions downstream of auxin in regulating LR formation; NO-inhibited seminal root elongation by decreasing meristem activity in root tips under –Fe, with the involvement of auxin.